Cu-doped NaNbO3 nanorods: Enhanced photocatalytic activity for RhB dye removal and antibacterial activity against E. coli - Fernandes, Daiane; Carvalho, Ramon D.; Trassante, Carla M.; Dias, Vagner da S.; Melo, Luize G.B.de; Raubach, Cristiane W.; Moreira, Mario L.; Jardim, Pedro L.G.; Ferrer, Mateus M.; Moreira, Eduardo C.; Graeff, Carlos Frederico de O. [UNESP]; Lund, Rafael G.; et al. (Elsevier, 2024)
Sodium niobate (NaNbO3) nanorods with Cu (0.00, 0.01, 0.02 and 0.04 mmol) insertion were prepared by the microwave-assisted hydrothermal method and the photocatalytic and antibacterial activity was explored for the first time. X-ray diffraction confirms the coexistence of two orthorhombic phases (P21ma and Pbma) for all samples, with the percentage of each phase being strongly influenced by doping. The micrographs reveal that doping did not alter the shape or size of the grains (nanorods, with a diameter of ∼200 nm and a length of tens micrometers). The samples of pure NaNbO3 and those with 0.01 and 0.02 mmol of Cu showed an average band gap value of 3.08 eV. However, the sample containing 0.04 mmol of Cu exhibited a slight redshift. The photocatalytic activity of the samples was assessed by the removal of Rhodamine B dye (RhB), under ultraviolet light. All doped samples exhibited superior performance, with the sample containing 0.02 mmol of Cu showing the best photocatalytic activity, achieving 100 % RhB removal in 50 min. This was attributed to a lower rate of recombination of photogenerated charges, as evaluated through photoluminescence analysis. Additionally, the photocatalyst demonstrated excellent recyclability over three cycles. Pure NaNbO3 nanorods showed no antibacterial activity, but doping with 0.04 mmol of Cu reduced the growth of Escherichia coli.
Keywords: Antibacterial activity; Cu-doping; Nanorods; Photocatalysis; Sodium niobate